Static hand sign recognition using linear projection methods - Gamage, Nuwan; Chow, Kuang Ye; Akmeliawati, Rini (2009)
Shape matching is one of the more significant research topics in the fields of Computer Vision, Pattern Recognition and Machine Learning. Successful shape matching algorithms/ methods has a high potential for a wide variety of practical applications. In this paper, we present our effort on using linear projection methods for static hand sign recognition in Malaysian Sign Language. PCA and LPP methods have been used with a database of 240 hand shapes.